Development of the oral, mental, and sexual reproductive health assessment tool for adolescents in Nigeria - Afolabi, Omorinola Adekemi; Chukwuemeka, Abel Nnamdi; Dabar, Anita Mofiyinfolu; Oveh, Richard Omoefe; Ibraheem, Saheed Ademola; Sam-Agudu, Nadia Adjoa; El Tantawi, Maha; Salako, Abideen Olurotimi; Eleje, George Uchenna; Lusher, Joanne; Ezechi, Oliver; Foláyan, Moréniké Oluwátóyìn (Frontiers in Oral Health, 2025)
BackgroundAdolescence is a critical developmental stage where oral, mental, and sexual and reproductive health are closely interconnected. However, these domains are often assessed in isolation, creating a gap in holistic adolescent health understanding and intervention. This study aimed to develop an integrated tool for assessing oral, mental, and sexual and reproductive health.MethodsA systematic literature review framework guided the study. Three dimensions—oral health, mental health, and sexual and reproductive health—were defined a priori. A structured search of PubMed and ScienceDirect identified relevant English-language articles and tools validated for use with adolescents in Nigeria. Deductive analysis was used for logical partitioning to identify items for domains and subscales. A preliminary questionnaire was drafted, organized into five sections: socio-demographics, oral health, mental health, sexual and reproductive health, and health service utilization. Items were matched with appropriate response scales.ResultsSeventy-eight articles were identified, and 43 met the inclusion criteria. From these, domains and subscales were adopted to construct an 81-item tool. Section one contains 21 socio-demographic items. Section two covers mental health with five constructs: psychological distress (12 items), depression (nine), generalized anxiety (eight), suicide ideation (four), and risk factors (alcohol, tobacco, psychoactive substance use, and self-esteem). Section three measures sexual and reproductive health with 11 items on sexual debut and activity status. Section four assesses oral health with eight items on oral hygiene, self-reported oral problems, and oral habits. Section five includes two questions on health service utilization, covering general, dental, and psychiatric services.ConclusionThis integrated 81-item tool captures three interconnected aspects of adolescent health, offering potential to strengthen service integration for this population. Beyond practice, it provides a foundation for empirical research to advance multisectoral adolescent health approaches. Future work should focus on validating the tool across diverse adolescent populations.